2020
DOI: 10.5455/jpma.16442
|View full text |Cite
|
Sign up to set email alerts
|

Five year evaluation of the complications observed in porcelain fused to metal (PFM) crowns placed at a university hospital

Abstract: Various complications are observed in the PFM crowns. These include chipped-off ceramic, recurrent caries and / or loss of retention. 4,5 Multiple factors are responsible for or are associated with these complications. These are broadly categorised as patient-related, operator-related and technician-related factors. Patient-related factors are para-function (clenching and bruxism), traumatic biting habits (biting on ice cubes, betel nuts etc.) and heavy occlusal forces. Operator-related problems include poor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 13 publications
2
5
0
2
Order By: Relevance
“…In the present clinical investigation 3, 6 and 12 months observational period of both groups, (table 2); no fractures were observed at metal ceramic crown, group (I). This is in agreement with short-term previous studies in which no fractures were reported (8,23) . On the contrary, IPS e.max press ceramic crown, group (II), exhibited higher fracture rates than metal ceramic crown when applied as single crown on first mandibular molar tooth, where fracture of five ceramic crowns was observed which are in disagreement with previous study (24) .…”
Section: Effect Of Materials Selection and Different Fabrication Techniques On Marginal And Internal Fit (397)supporting
confidence: 94%
See 1 more Smart Citation
“…In the present clinical investigation 3, 6 and 12 months observational period of both groups, (table 2); no fractures were observed at metal ceramic crown, group (I). This is in agreement with short-term previous studies in which no fractures were reported (8,23) . On the contrary, IPS e.max press ceramic crown, group (II), exhibited higher fracture rates than metal ceramic crown when applied as single crown on first mandibular molar tooth, where fracture of five ceramic crowns was observed which are in disagreement with previous study (24) .…”
Section: Effect Of Materials Selection and Different Fabrication Techniques On Marginal And Internal Fit (397)supporting
confidence: 94%
“…In the current investigation, survival rate of metal ceramic crowns, group (I) was 98% which is consistent with previous data published in scientific literature (8,23) . While the overall success rate was 75% which is in disagreement with previous studies that reported higher success rate than present study (8,26) .…”
Section: Effect Of Materials Selection and Different Fabrication Techniques On Marginal And Internal Fit (397)supporting
confidence: 92%
“…Today, one of the most popular and usable restorations is ceramic metal restoration, which combines the power and precision of metal casting with the beauty of porcelain. Porcelain-fusedto-metal (PFM) has long been used in clinical practice and is therefore considered the standard material for implantsupported restorations [18].…”
Section: Type Of Restorationmentioning
confidence: 99%
“…3 Various studies have reported a higher incidence of mechanical complications leading to failure of fixed restorations. [4][5][6] Mechanical problems include, but are not limited to, de-cementation of crowns, loss of retention, marginal discrepancies, abutment fractures, porcelain fractures, fracture of metallic connectors etc. 4 Jamal et al, 5 advocated that open proximal contacts, loss of retention and ceramic fracture were the major causes leading to compromises in the way of the success of FDPs.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Mechanical problems include, but are not limited to, de-cementation of crowns, loss of retention, marginal discrepancies, abutment fractures, porcelain fractures, fracture of metallic connectors etc. 4 Jamal et al, 5 advocated that open proximal contacts, loss of retention and ceramic fracture were the major causes leading to compromises in the way of the success of FDPs. Ghani et al, 2 published similar results, reporting that majority of the crowns faced complications due to de-cementation (24.8%).…”
Section: Introductionmentioning
confidence: 99%